Pemodelan UML dan Perancangan Sistem Informasi Praktek Kerja Lapangan Pada Sekolah Menengah Kejuruan (Current Research in Education: Conference Series Journal, 2022)
Job Training (PKL) is an implementation of a systematic and synchronous implementation of educational programs in schools, especially in Vocational High Schools (SMK) with mastery of skills acquired through direct work activities in the workplace to achieve a certain level of expertise. In addition, PKL is one of the academic activities that all SMK students must participate in in the school's existing programs. PKL places are companies or agencies that collaborate with schools. Companies and internships can only accept interns for a maximum of 30% of the total number of employees. In this study the authors analyzed and designed a WEB-based street vendor information system starting from the student registration process, implementation and reporting, and PKL assessments. This study aims to organize PKL activities neatly between students, companies and schools where they are apprenticed so that all parties can benefit from PKL activities.